Incidental catches of dolphins in mid-water trawls for Argentine anchovy (Engraulis anchoita) off the Argentine shelf - A. Crespo, Enrique; Koen-Alonso, Mariano; Laura Dans, Silvana; A. Garcia, Nestor; N. Pedraza, Susana; Coscarella, Mariano; González, Raúl (J. Cetacean Res. Manage., 2000)
Information on the incidental mortality of dusky and common dolphins in mid-water trawl fisheries along the Argentine shelf was obtained for the 1990s. The Argentine anchovy is believed to be an under-exploited resource and is usually taken in purse seine fisheries. However, on the few occasions when it was the target species of large mid-water trawlers, anchovy-eating dolphins were incidentally caught. A few incidents accounted for relatively high numbers of dolphins but in most of the cases the information obtained was insufficient for detailed analysis. For three cases, however, sufficient information was obtained to estimate mortality rates. Nevertheless, interpretation of these rates is difficult for a number of reasons. FV Mar Salvaje caught around 60 common dolphins (Delphinus delphis) in only a few days and in one tow 20 dolphins were caught. Biological information on 18 common dolphins (12 males and 6 females) was obtained and ages ranged from 5-10 for females and 2-18 for males.